Effect of Pre-milling Treatment and Abrasive Roller on Milling of pulses - Mangaraj, S; Agrawal, S; Kapoor, T; Kulkarni, S D (Journal of Agricultural Engineering, 2004)
The possibility of improving the pulse milling efficiency and dal recovery was attempted by reducing the losses using different carborundum grade rollers (8, 16, 24, 32, 40) and pretreatments (conventional, CIAE, millers practice) for three pulses - pigeon pea, chickpea and green gram. Moisture content of sample was kept at 9% (db) for milling studies using CIAE dal mill. The head dal recovery of 81% for pigeon pea and 79% for chick pea was obtained using 32 grade for roller and CIAE milling method and 81% for green gram using 40 grade for roller and millers practice method. The milling efficiency for pigeon pea, chickpea and green gram was found to be 83.16%, 81% and 88% respectively using millers practice.